Analysis of Security Mechanisms Based on Clusters IoT Environments - Montenegro-Marin, Carlos Enrique; Gaona-García, Paulo Alonso; Prieto, Juan David; Nieto Acevedo, Yuri Vanessa (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
Internet of things is based on sensors, communication networks and intelligence that manages the entire process and the generated data. Sensors are the senses of systems, because of this, they can be used in large quantities. Sensors must have low power consumption and cost, small size and great flexibility for its use in all circumstances. Therefore, the security of these network devices, data sensors and other devices, is a major concern as it grows rapidly in terms of nodes interconnected via sensor data. This paper presents an analysis from a systematic review point of view of articles on Internet of Things (IoT), security aspects specifically at privacy level and control access in this type of environment. Finally, it presents an analysis of security issues that must be addressed, from different clusters and identified areas within the fields of application of this technology.
Keywords: information technology; security; internet of things; network; data security; IJIMAI